The effect of trust, customer satisfaction and image on customers’ loyalty in Bank Islam Jasin Melaka / Muhamad Sukur Mihat - Mihat, Muhamad Sukur (Faculty of Business and Management, 2011)
This research attempts to find the level of customer loyalty and their relationship in Bank Islam Melaka. In order to do this, a questionnaire is designed and validated, then based on the data which is gained from the sample of 60 respondents that is volunteered to complete multiple self-administered questionnaire for the data collection process, the analysis is done and the result and the relation among the factor are explained. Data was then aggregate and analyzed using descriptive analysis, and correlation. Trust, customer’s satisfaction and image are the factor that influences customer’s loyalty of customer in Bank Islam in this study. These factor are influence each other as well. The relationships of different factor with each other are also studied and the SPSS software is used to analyze the data gathered from the respondents. From the study, it was found that most of the customer in Bank Islam had experienced high level in customer loyalty whereas the other considered as moderate. Beside that, all of the relationship between independent variable was positively significant toward customers’ loyalty in Bank Islam Jasin. The result demonstrate that most of the customer are trusted and satisfied, however the possibility of customer dissatisfied of the banks is always exist.